Strategi Pembelajaran Berbasis Psikologi Humanistik Untuk Meningkatkan Keterlibatan Siswa - Wargo Silanto; Dedi Kuswandi; Ika Andrini Farida (Institut Agama Kristen Negeri (IAKN) Ambon, 2025)
Abstract: Student engagement is an important indicator of learning effectiveness; however, various reports show that active student participation in Indonesia remains low. This literature review analyzes the role of humanistic psychology based learning strategies in enhancing student engagement across cognitive, affective, and behavioral dimensions. Humanistic psychology, rooted in the ideas of Maslow and Rogers, emphasizes the fulfillment of basic needs, authentic interpersonal relationships, and emotionally safe learning environments as the foundation of meaningful learning. The findings of the literature review indicate that strategies providing autonomy, empathetic communication, reflective learning, and contextual learning experiences can enhance intrinsic motivation, learning interest, and students’ active participation. Several studies also highlight that the quality of teacher student relationships is a decisive factor in engagement, particularly through emotional support, constructive feedback, and a positive classroom climate. In the digital era, the integration of technology that preserves humanistic values has also been shown to strengthen student engagement. Overall, these findings suggest that the humanistic approach makes a significant contribution to improving student engagement and is relevant for application in modern education. This research provides a theoretical and empirical foundation for developing learning practices that are more humanistic, empowering, and oriented toward learners’ needs. Keywords: humanistic psychology, learning strategies, student engagement, intrinsic motivation